Comparison of the modified Singapore myocardial infarction registry risk score with GRACE 2.0 in predicting 1-year acute myocardial infarction outcomes - Sia, Ching-Hui (NATURE PORTFOLIO, 2022)
10.1038/s41598-022-16523-6